THE EFFECT OF PARACETAMOL AND CODEINE ANALGESIC COMBINATION ON SERUM GLUTAMIC OXALOACETATE TRANSAMINASE LEVELS IN MALE WISTAR RATS - Rona Ayu Hanifah; Farah Hendara Ningrum; Erwin Kresnoadi; Satrio Adi Wicaksono (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Introduction : Paracetamol is an effective analgesic to relieve mild to moderate pain when it is used in therapeutic doses. Codeine is an opioid analgesic to relieve moderate to severe pain. Both are metabolized in the liver and have different mechanisms in the treatment of pain. The use of paracetamol and codeine as monotherapy has been extensive, but research on the effectiveness of these drugs in combination is still limited, especially about its effect in liver damage. This study was to investigate the effect of paracetamol and codeine analgesic combination Serum Glutamic Oxaloacetate Transaminase levels in male Wistar rats. Method : This was an experimental study using Post-Test Only Control Group Design. The samples were 24 male wistar rats randomized into 4 groups; group I (control group, without treatment), group II receiving paracetamol 32 mg/kgBB, group III receiving codeine 1,9 mg/kgBB, and group IV receiving combination of paracetamol 32 mg/kgBB and codeine 1,9 mg/kgBB. Drugs were administered through oral gastric instillation 4 times a day for 28 days. Blood samples were collected at the 29th day through retroorbital vessel to measure the SGOT levels. The data was analysed using One-Way ANOVA test and Post-Hoc test. Results : The results of this research were obtained from statistical tests where there was no significant increase of the levels of Serum Glutamic Oxaloacetate Transaminase of Wistar rats which received a combination of paracetamol and codeine in the control group (p = 0.005). While in the other group there was not significant differences of the levels of Serum Glutamic Oxaloacetate Transaminase. Conclusion : There is no significant difference of Serum Glutamic Oxaloacetate Transaminase levels between the administration of paracetamol and codeine combination compared to the control group.Keywords : Paracetamol, codeine, paracetamol and codeine combination, SGOT levels, pain